2022
DOI: 10.1093/brain/awac220
|View full text |Cite
|
Sign up to set email alerts
|

The kappa free light chain index and oligoclonal bands have a similar role in the McDonald criteria

Abstract: Intrathecal production of kappa free light chains (KFLC) occurs in multiple sclerosis and can be measured using the KFLC index. KFLC index values can be determined more easily than oligoclonal bands (OB) detection and seem more sensitive than the immunoglobulin (Ig)G index to diagnose multiple sclerosis. We assessed the value of OB, KFLC index cut-offs 5.9, 6.6, and 10.61, and IgG index to diagnose multiple sclerosis with prospectively acquired data from a clinically isolated syndrome (CIS) inception cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 54 publications
3
28
0
2
Order By: Relevance
“…Furhtermore, KFLC-index has been recently shown to predict or be associated with early inflammatory disease activity (19,22,24), and in the present study we show that high levels are predictive of cognitive decline. We have previously shown that treatment with fingolimod and alemtuzumab did not influence KFLC-index levels (18).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furhtermore, KFLC-index has been recently shown to predict or be associated with early inflammatory disease activity (19,22,24), and in the present study we show that high levels are predictive of cognitive decline. We have previously shown that treatment with fingolimod and alemtuzumab did not influence KFLC-index levels (18).…”
Section: Discussionsupporting
confidence: 77%
“…Kappa free light chain (KFLC) index ([CSF KFLC/serum KFLC]/ [CSF albumin/serum albumin]), a marker for intrathecal production of free kappa chains, has been increasingly recognized in recent years for its diagnostic (16)(17)(18)(19)(20) and prognostic (21)(22)(23)(24)(25) potential in RRMS. Although the association between intrathecal Ig synthesis as determined by IgG-OCBs and CI has been previously studied (26,27), the prognostic role of KFLC synthesis in relation to CI remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adding OCB to KFLC biomarkers may be helpful in atypical cases. Based on our results, the results of other diagnostic studies, [7][8][9][10][11][12][13][14] the ones of predictive studies, 21,23,34 and the knowledge into MS red flags, 1,35,36 we propose an algorithm that integrate KFLC biomarkers to diagnose MS (eFigure 3, links.lww.com/NXI/A753).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, predictive studies 23,34 found that KFLC index predict second clinical attack or MRI dissemination in space and time, in patients with CIS, with a good accuracy, slightly better than OCB. 23,34 Because KFLC measurement is an easier way to prove intrathecal B-cell activity, with at least as good diagnostic performances than OCB, KFLC index or KFLC IF could be used in clinical practice instead of OCB as first-line MS biomarker. Nonetheless, using a combination of KFLC and OCB significantly increases specificity for MS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation